2021
DOI: 10.1002/adfm.202103445
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Organic Solar Cells Based on Asymmetric Acceptors Bearing One 3D Shape‐Persistent Terminal Group

Abstract: Three asymmetric non-fullerene acceptors (LL2, LL3, and LL4) are designed and synthesized with one norbornyl-modified 1,1-dicyanomethylene-3indanone (CBIC) terminal group and one chlorinated 1,1-dicyanomethylene-3-indanone (IC-2Cl) terminal group. The three-dimensional shape-persistent CBIC terminal group can effectively enhance the solubility and tune the packing mode of acceptors. Compared with their symmetric counterparts (LL2-2Cl, LL3-2Cl, and LL4-2Cl) bearing two IC-2Cl terminals, the asymmetric acceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…The above results suggest that higher crystallinity and more ordered packing structure is formed in PBDB‐T: SM16 ‐based blend film by the incorporation of norbornenyl motifs, being beneficial for realizing high μ h and μ e . [ 29,47 ] We also notice that the π–π stacking distance is shorter in the PBDB‐T: SM16 blend film (3.67 Å) than that in the pristine SM16 film (3.73 Å). On the contrary, the π–π stacking distance (3.64 Å) in the PBDB‐T: SM16‐R blend film is larger than that in the pristine SM16‐R film (3.61 Å).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The above results suggest that higher crystallinity and more ordered packing structure is formed in PBDB‐T: SM16 ‐based blend film by the incorporation of norbornenyl motifs, being beneficial for realizing high μ h and μ e . [ 29,47 ] We also notice that the π–π stacking distance is shorter in the PBDB‐T: SM16 blend film (3.67 Å) than that in the pristine SM16 film (3.73 Å). On the contrary, the π–π stacking distance (3.64 Å) in the PBDB‐T: SM16‐R blend film is larger than that in the pristine SM16‐R film (3.61 Å).…”
Section: Resultsmentioning
confidence: 80%
“…To the best of our knowledge, this is the highest value for PBDB-T-based OSCs. [28][29][30] It can be seen from the three photovoltaic parameters that the enhancement of both V oc and FF contribute greatly to the improvement of device mance. To explore the origin of the higher V oc in ternary OSCs with respect to PBDB-T:Y14-based binary OSCs, the ΔV nr values of both binary and ternary OSCs were determined by their EQE EL values according to Equation (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, two strategies have been proposed to decrease the energy losses of OSCs: 1) narrowing the energy level offset between acceptor and donor, to minimize the driving force for charge generation; 2) enhancing EQE EL of the donor:acceptor blend. [ 38–46 ] For the former, both our lab and other groups revealed that, with a minor highest occupied molecular orbital (HOMO) offset close to zero (0–0.1 eV), rapid hole transfer from acceptor to donor or a sufficient charge generation process still took place. [ 36,47 ] Considering that the classic PM6:Y6 blend is reported to have the HOMO offset in the range of 0.09–0.20 eV, [ 24,41,44 ] it seems that there is still a room to reduce the energy loss of OSCs if the newly designed acceptor owns a HOMO level nearly flat with PM6.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of NFAs can be modified by changing the central core units, side chains, and terminal groups. ,, High-performance A–D–A-based NFAs such as ITIC and Y6 have been constructed with a fused ring central core and two flanking terminal acceptor units. To improve the device performance of OSCs, A−π–D−π–A-type NFAs have been synthesized by inserting aromatic π-bridge units between the D and A moieties, which can effectively tune the absorption properties, energy levels, intramolecular charge transfer properties, and molecular packing of the NFAs. , For instance, π-bridging units such as thiophene, thieno­[3,4- b ]­thiophene, and benzoxadiazole have been used to develop NFAs. , Yao et al reported the design of IEICO-4F by inserting a 3-(2-ethylhexyloxy)­thiophene π-bridge, which resulted in a power conversion efficiency (PCE) of ∼12% . Liu et al modified 3-alkoxythiophene to 4-alkoxythiophene on the π-bridging unit in IEICO-4F, and the resulting IDTCN-O offered a higher PCE of 13.28% due to improved solubility and better blend film morphology .…”
Section: Introductionmentioning
confidence: 99%